Consumer ratings and the pricing of experience goods: hedonic regression analysis of beer prices - Rachel A. Smith; C. Nicholas McKinney; Steven B. Caudill; Franklin G. Mixon (Agricultural and Food Economics, 2016)
This study fills a void in the literature by providing the first evaluation of the impact of consumer ratings on beer prices using hedonic methods. Our work is based on a dataset consisting of over 400 beers and includes information on calorie content, alcohol content, user rating, and style for each beer. Our results indicate that a 10-point increase in consumer rating is associated with about a 0.50 increase in the price of beer per unit.
Keywords: 330; Experience goods; Hedonic analysis; Beer prices; Consumer ratings; Asymmetric information